Boosting Novice Voters: Strategy of the Independent Election Commission for the 2024 General Election in West Aceh District - Alfi Mansyur; Vellayati Hajad (Politicos: Jurnal Politik Dan Pemerintahan, 2024)
This comprehensive study examines the strategies employed by the Independent Election Commission (IEC) to boost the participation of novice voters in the pre-election phase leading up to the 2024 General Election in West Aceh District. Novice voters aged 17 to 21 play a significant role in measuring electoral efficacy and vitality. Recognized by political stakeholders, their engagement affects the electoral landscape due to their diverse characteristics and challenges compared to previous generations, such as lack of interest, awareness, knowledge, and apathy. So, this research was carried out to analyze the strategies used by the IEC towards novice voters. This study adopts David's (2004) strategy theory in strategic management, which includes formulation, implementation, and evaluation. Conducted in West Aceh Regency, this study examines the initiatives and challenges of the IEC in engaging novice voters. Through careful empirical data analysis, this study aims to improve the electoral process and consolidate democracy in Indonesia. The research findings reveal insights into the effectiveness of the IEC's strategies and highlight areas for improvement. This study provides valuable insights for future election planning, encouraging more equitable and inclusive practices. However, several problems in its implementation need to be resolved, mainly the need for more human resources and budget.